The improvement and systematization standard base for activity to live of the Ukrainian Antarctic Expeditions – the pledge of successful performance of the State Scientific and Technical Program of the Ukrainian Researches in Antarctica - Moroz, I.; Gavryliuk, B. (Ukrainian Antarctic Journal, 2012)
The aspects of improvement and ordering of standard base for ability to live of Ukrainian Antarctic Expedition are considered in article. The activity rationing process of Base Commanders of Ukrainian Antarctic Station «Akademik Vernadsky» and all expedition members is described here in base routines and emergency situation. The experience of BAS has been analysed. The article exposes the structure and history of creation of the «Base commander Handbook», BAS document.